Sistem panic button - Chairul Yusuf Dau; Agus Lahinta; Edi Setiawan (Gorontalo State University, 2021)
Abstract Disaster often appear in the news media, ranging from floods, fires, landslides and tsunamis or other disasters. At the time of the accidents that came to happen perhaps people will forget the circumtances around it, because they think about their own safety and belongings. Therefore, it requires a system that can help community in calling for assistance to the disaster management. The aims of thi s study is to augment community choice in asking for help from disaster management. The results in this study is a Panic Button System that can help the community and the disaster management in handling disaster that occur.Keywords: Pannic Button, Natural Disaster yg